Safety and Efficiency of Trabectome-mediated Trabecular Meshwork Ablation for Chinese Glaucoma Patients: A Two-year, Retrospective, Multicentre Study - Ya-Long Dang; Yu-Jie Cen; Ying Hong; Ping Huang; Ning-Li Wang; Chao Wang; Chun Zhang; China Trabectome Study Group (Chinese Medical Journal, 2018)
Background: The aim of the study was to evaluate the long-term safety and efficacy of the Trabectome for Chinese glaucoma patients. Methods: This was a multicenter, retrospective, observational study. Glaucoma patients, except those with neovascular glaucoma, with/without a visually significant cataract were enrolled. The patients received Trabectome or a combined surgery with phacoemulsification and intraocular lens implantation. The primary outcome evaluation was a reduction in intraocular pressure (IOP), and the secondary outcomes were a reduction in glaucoma medication, the 2-year success percentages, and complications. Success was defined as an IOP <21 mmHg and at least a 20% IOP reduction from baseline after 3 months for any two consecutive visits, without additional glaucoma surgery. The data were processed using the R Stats Package version 3.0.0. The Wilcoxon test was used to compare the postoperative IOP and the number of glaucoma medications with baselines. The Kaplan–Meier test was used to calculate the 2-year success percentage. The risk factors related to Trabectome failure were determined by logistic regression. Results: A total of 120 glaucoma patients were enrolled. The Trabectome efficiently reduced the IOP from a baseline of 22.8 ± 1.34 mmHg to 17.6 ± 0.96 mmHg, and the use of glaucoma medications from 2.2 ± 0.17 mmHg to 1.4 ± 0.21 in a 2-year follow-up (both, P < 0.01). The overall success percentage was 80%. No risk factor related to Trabectome failure was identified. No vision-threatening complication was observed. Ten patients, who required secondary glaucoma surgery, all reached the target IOP. Conclusions: In a 2-year follow-up, Trabectome was an efficient and safe procedure for Chinese glaucoma patients.